A high-performance solid sodium battery enabled by a thin Na-Ti3C2Tx composite anode. (20th December 2022) - Lu, Liang; Yuan, Hao; Sun, Chunwen; Zou, Bingsuo
Abstract: Low-cost sodium metal batteries are expected to be used as an effective supplement to lithium-ion batteries in the energy storage field in the future, and have made great progress in recent years. However, the safety issues caused by Na dendrites and the relatively low specific capacity of sodium metal batteries are obstacles to their further commercialization. In this work, a thin Na-Ti3 C2 Tx composite anode was prepared. The thickness of the composite anode Na-Ti3 C2 Tx is only 46% of that of pure sodium, greatly reducing costs and increasing energy density. In addition, the nucleation overpotential of Na-Ti3 C2 Tx is 55.2% and 56% that of Na at 0.5 mA cm −2 and 2 mA cm −2 respectively, which indicates that the composite anode reduces the sodium nucleation barrier and is favorable for sodium deposition. Furthermore, the poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) and Na3 Zr2 Si2 PO12 modified polyimide membrane significantly enhances the mechanical strength and sodium ion migration and promoted the deposition and stripping of metallic sodium. The sodium battery with the composite metal sodium anode and PVDF-HFP-Na3 Zr2 Si2 PO12 modified polyimide membrane has a specific discharge capacity of 87.9 mAh g −1, and the capacity retention rate is close to 100% without significant fluctuation after 500 cycles. Table of Contents: A thin Na-Ti3 C2 Tx composite anode was prepared. It can significantly reduce the nucleation overpotential of sodium. The sodium metal battery with the composite metal sodium anode and PVDF-HFP- Na3 Zr2 Si2 PO12 modified polyimide membrane has a specific discharge capacity of 87.9 mAh g −1 and shows excellent cyclability over 500 cycles. The prepared ultra-thin sodium anode can effectively reduce the use of metal sodium and improve the energy density of the battery, which is of great significance for promoting the industrialization of sodium metal batteries. Image, graphical abstract